Rekonstruksi Perlindungan Hukum Hak Ekologis Masyarakat Adat Pesisir dalam Pelaksanaan Proyek Strategis Nasional (Studi Kasus Suku Laut di Bintan) - Alfin Dwi Novemyanto (JURNAL HUKUM PELITA, 2025)
This study examines the reconstruction of legal protection for the ecological rights of coastal Indigenous communities within Indonesia’s National Strategic Projects (NSP), using the Sea People (Suku Laut) of Bintan as a case study. The displacement of traditional settlements and coastal ecosystem degradation reveal the weakness of ecological rights enforcement and Indigenous participation in environmental licensing. Employing a normative legal method with statutory, conceptual, and case approaches, this research explores the gap between constitutional norms and administrative practice. The analysis applies ecological justice and good environmental governance theories to evaluate constitutional, administrative, and participatory dimensions of Indigenous environmental protection. Findings indicate a persistent legal vacuum and overlapping authority obstructing the recognition of marine customary rights and the enforcement of Free, Prior, and Informed Consent (FPIC) principles. A collaborative legal model is proposed, integrating ecological justice, independent coastal oversight institutions, and collective-rights-based regulations. This research recommends comprehensive legal reform toward an ecologically just and participatory coastal governance framework